Availability and Accesibilty of E- Resources in Nigeria Libraries: Certified Librarians Perspetive - Saliu, Sambo, Atanda; Stella, Ejitagha; Promise, Aworo (American Journal of Social Sciences and Humanities, 2016)
This paper presents the results of a cross section survey of librarians designed to investigate availability and accessibility of e- resources in Nigeria Libraries. A social survey method of research was adopted for the study and the questionnaire as a research instrument was used. A systematic random sampling technique was used to determine respondents in the survey. The result revealed that availability and accessibility of e- resources are yet to be available and accessible to some libraries in Nigeria despite the fact that 56% of the respondents attested that e- resources are very much available and accessible in their libraries. Likewise, findings revealed that majority of the participants were academic staff 56% while 46% are non- teaching staff. The findings showed that e - resources are available in two major formats PDF and HTML whereas 67% of respondents preferred PDF format for accessing e-resources, whereas 26% of respondents preferred HTML format; and 7% have no preference. It also, indicated that majority 55% of respondents are highly satisfied with the infrastructure provided by the libraries for accessing e-resources at different levels. The study recommends that Library Stakeholders, libraries management and librarians should ensure that e-resources were available and accessible to others libraries were e-resources are lacking for efficiency and effective service delivery among others.